Myopia and/or longer axial length are protective against diabetic retinopathy: a meta‐analysis. (7th November 2015) - Fu, Yu; Geng, Dengfeng; Liu, Hua; Che, Huixin
Abstract: Purpose: To evaluate the current evidence of the relationship between myopia, together with its structural and refractive component, and diabetic retinopathy (DR) risk. Methods: A systematic search was performed up to April, 2015. Summary odds ratios (ORs) and 95% confidence intervals (CIs) were calculated employing random‐effects models. Three models were used to assess the association between myopia and risk of DR: axial length (AL) (per millimetre increase) and DR; myopia (myopia versus non‐myopia) and DR; refractive error (RE) (per D decrease) and DR. Publication bias of the literature was evaluated using Begg's funnel plots and Egger's test. Results: A total of 11 studies that met the predefined criteria were included in this meta‐analysis. Overall, longer AL (per millimetre increase) was associa‐ted with a significantly decreased risk of DR (combined OR, 0.75; 95% CI, 0.65–0.86; p < 0.001); myopic eyes (myopia versus non‐myopia) showed a lower risk of DR (combined OR, 0.70; 95% CI, 0.58–0.85; p < 0.001). A greater degree of myopic RE (per D decrease) also revealed a significantly decreased risk of DR (combined OR, 0.89; 95% CI, 0.85–0.93; p < 0.001). The sensitivity analyses and cumulative meta‐analysis showed similar results. No publication bias was detected in any of the three models. Conclusions: This meta‐analysis suggests that both myopic refraction and longer AL are associated with a lower risk of DR. Further studies are needed to determine exact mechanisms underpinning the protective effect of myopia against DR.